Victims of the NKVD Katyn Operation from among Lithuanians and Residents of the Former Wilna Province of the Second Polish Republic - Jasiewicz, Krzysztof (Genocidas ir rezistencija, 2019)
The German Treaty of Non-Aggression of 23 August 1939, signed in Moscow by Joachim von Ribbentrop and Vyacheslav Molotov, defined the spheres of influence of the contracting parties and effectively signalled the beginning of World War II. At the same time, the Pact initiated the tragedy of millions of Central and Eastern Europeans, including the people of Lithuania and Poland. The Soviet government wanted to eradicate those who did not fit the Soviet model, so they were deported en masse and exterminated in Soviet-occupied Poland and Lithuania. One of the greatest symbols of such crimes is Katyn massacre. The fate of these people was determined by the Soviet military imperialist doctrine.